Pengaruh Brand Image Terhadap Keputusan Pembelian Konsumen Pada Busana Muslim Di Elzatta Palembang - Melinda Adelia Melin; Nurseri Hasna Nasution (Social Science and Contemporary Issues Journal, 2023)
This research aims to determine and analyze consumer perceptions of the Elzatta brand image, consumer decisions in purchasing Elzatta products, and how much influence the brand image has on consumer purchasing decisions for Muslim clothing at Elzatta Palembang. This research uses quantitative methods. data collection by distributing questionnaires to 85 respondents. From the research results obtained from brand image, 53 respondents (62%) were in the medium category and for purchasing decisions, 51 respondents (60%) were in the medium category. The results of this research were obtained. Data were analyzed using Instrument Tests, Basic Assumption Tests, and Hypothesis Tests using data processing assisted by the SPSS version 26 software program. The research results showed that there was an influence of Brand Image (X) on Purchasing Decisions (Y). This is proven by the t test (partial) which obtained tcount of 7.916, which means tcount 7.916 > ttable 1.663, and the coefficient of determination (R Square) value of 0.430 (equivalent to 43%), which means there is a large influence. The magnitude of the influence of the Brand Image variable (X) on Purchasing Decisions (Y) is 43%, while the remaining 57% is influenced by other factors not researched.